Grazing behavior of Maasai cattle - Semenye, P.P. (International Livestock Centre for Africa, 1988)
The grazing behaviour of Maasai cattle was influenced by season, area and grazing orbit. In a grazing day the cattle spent 1, 8, 14, 15 and 62 percent of their time drinking, ruminating, resting, walking and grazing respectively. The mean length of the grazing day of Maasai cattle is defined, as from the time they left their bomas in the morning until they returned for the night; this duration was 10.8 plus or minus 0.6 and and 10.4 plus or minus 0.6 hours for cattle and calves respectively. The mean grazing orbit was 15.5 and 10.8 km for adult cattle and calves respectively. A vibracorder proved quite accurate in timing cattle activities.